Bee guards detect foreign foragers with cuticular chemical profiles altered by phoretic varroa mites. Issue 3 (22nd August 2016) - Cappa, Federico; Bruschini, Claudia; Protti, Ilaria; Turillazzi, Stefano; Cervo, Rita
Abstract : Detection of diseased individuals in a social group is a critical step of social immunity, to prevent the spread of parasites or pathogens. Parasite-induced alterations of the host phenotype might be used by healthy conspecific to identify an individual bearing a threat to the social group, and to prevent it from entering the colony. The ecto-parasitic varroa mite ( Varroa destructor ) is a crucial driver for the extensive worldwide honey bee losses, and the parasite is currently considered one of the major threats for apiculture. Here, we first investigated the alterations induced by phoretic varroa mites on the cuticular hydrocarbons profile of adult honey bees. Our gas chromatography–mass spectrometry analyses showed an increase in cuticular methyl-branched compounds of parasitized bees. Then, we used lure presentation experiments to evaluate the response of guard honey bees at the hive entrance towards foreign foragers with a parasite-altered cuticular profile. We found an increase in the aggressive responses of guard bees towards bee-lures with a parasite-altered cuticular profile, highlighting the ability of Apis mellifera guard bees to recognize the alterations induced by varroa in the cuticular profile of alien bees.